A study of trends and projection of life expectancy and its association with socio-demographic index: Results from GBD study 2023 - Reza Taherian; Maryam Karimi Ghahfarokhi; Farid Zayeri (PLoS ONE, 2026)
Background Life expectancy (LE) serves as a central indicator of population health, reflecting the combined effects of social, economic, and demographic factors. Despite global improvements, substantial disparities persist across regions and development levels. This study aims to analyze temporal and spatial trends in life expectancy at birth (LEB) and assess its relationship with the Socio-Demographic Index (SDI) from 1960 to 2023, with projections to 2050. Methods LE data for 190 countries from 1960 to 2023 were obtained from Our World in Data, while the SDI, reflecting overall social and economic development, was derived from GBD data. Joinpoint regression models were used to estimate annual and average annual percentage changes (APC, AAPC) across countries, regions, and SDI groups. Correlation analyses assessed the strength of association between LEB and SDI. Future trends were projected using a Bayesian Age-Period-Cohort (BAPC) model, generating estimates up to 2050 with 95% credible intervals. Results Global LE increased steadily from 1960 to 2023, with an overall AAPC of 0.58%. Despite this progress, large regional and socio-demographic gaps persist. Lower-SDI and low-income regions exhibited faster relative growth but greater fluctuations, whereas higher-SDI regions demonstrated slower yet stable improvement. The correlation between LEB and SDI remained strong throughout the study period (r = 0.82–0.90). Projections from the BAPC model indicate continued increases in LE, from 73.6 years in 2025 to 82.8 years in 2050, although uncertainty widens toward mid-century, reflecting potential divergence in global health trajectories. Conclusion LE has improved globally but remains uneven across socio-demographic contexts. Strengthening social and economic systems, expanding equitable healthcare access, and integrating SDI-based evidence into policy frameworks are essential to sustain progress toward health equity and longevity through 2050 and beyond.